Strengthening the Understanding of the Qur'an with the Use of Indonesian Assisted by the Millionaire Quiz Game Application - Restiani M. S.; Teti Sobari; Reka Yuda Mahardika (IKIP Siliwangi, 2026)
In the learning process, the TPQ language of instruction often uses regional languages ​​and Arabic. This is one of the obstacles for students who do not understand Arabic and regional languages ​​because they come from various backgrounds so they have difficulty understanding Al-Qur'an material. This research aims to strengthen understanding of the Al-Qur'an in the Al-Qur'an Education Park using Indonesian based on the billionaire quiz game application. This research used a quantitative approach carried out at the Al-Qur'an Education Park at the Darul Falah Islamic Boarding School, West Bandung. The method in this research uses a survey method and an independent sample t-test. The population in this study was all students at the Darul Falah Islamic Boarding School. The sample in this study consisted of male and female students in classes V A and V B, numbering 15 and 20 for a total of 35 students. In this study, it can be concluded that the average scores obtained by male and female students were 82.67 and 850. Meanwhile, the standard deviation scores were 5,627 and 5,104 with a total of 2,996. In the research, it was found that the pretest and posttest scores showed that there was no correlation or significant difference in the understanding of the Qur'an in the use of Indonesian based on the millionaire quiz game application.